REDESIGN OF SEWING OPERATOR SEAT USING REVERSE ENGINEERING METHOD - Hidayat Hidayat (Universitas Trunojoyo Madura, 2022)
We often see that many of the chairs that tailor tend to have a long shape and the width of the seat is quite narrow. The problem of working attitude faced by the sewing machine while running from a non-ergonomic work chair is the attitude of forced labor such as: lifting the operator up, and lifting the shoulder. If the ergonomic problem is not corrected, it will certainly give an excessive burden, musculoskeletal complaints which will be followed by a decrease in the level of work productivity. Therefore, it is necessary to conduct research in an effort to overcome the problems that arise. For this purpose, research was conducted on the Development and Design of Sewing Operator Chairs Using the Reverse Engineering Method. The number of research samples taken were 26 operators. In this study, it was found that there were 5 parts of the operator's seat that were repaired, namely in the seat connection, seat support mat, backrest, seat mat, and frame. And for the Popliteal Length percentile data at the 50th percentile, Hip width using the 95th percentile, Popliteal height using the 50th percentile.